ELECTION OF REGIONAL HEAD BASED ON HIERARCHY: STRENGTHENING ARGUMENTATION OF THE DISCUSSION OF ABOLISHING DIRECT ELECTIONS IN INDONESIA AND PROPOSED MODELS: PEMILIHAN KEPALA DAERAH BERBASIS HIRARKI: PENGUATAN ARGUMENTASI WACANA PENGHAPUSAN PILKADA LANGSUNG DI INDONESIA DAN USULAN MODEL - Taufik Hidayat; Lia Fitrianingrum (Constitutional Law Society, 2022)
Since the direct election of regional heads (Pilkadasung) has resulted in six major problems. These six big problems gave birth to the discourse of eliminating the Pilkadasung in Indonesia, and replacing it with a new system that is still within the corridors of democracy. The formulation of the problem in this paper are: (1) what arguments can be given in order to strengthen the discourse on the abolition of the Pilkadasung?, and (2) the proposed model that can be given as a substitute for the abolition of the Pilkadasung?. This paper is a conceptual study. Based on state administration practices that occur in the Special Region of Yogyakarta, where the election of regional heads uses the determination method, where Sri Sultan Hamengkubuwono and Sri Paku Alam are appointed by the President as Governor and Deputy Governor (DIY). As well as. practice of state administration in the Special Capital Region of Jakarta, where the Mayor is appointed by the Governor. Then, based on the theory from Manor and Crook. Strengthening the argument that the Pilkadasung is not the only way that is the most democratic, so alternative models can be used with other systems. In an effort to eliminate the six major problems of the Pilkadasung, the proposed model proposed in this paper is a hierarchy-based regional head election. The Governor is appointed by the President, and the Mayor/Regent is appointed by the Governor. The appointment process uses the following mechanisms: (1) an open position auction, (2) a public hearing, and (3) a fit and proper test at the Provincial DPRD for the Governor and at the City/Regency DPRD for the Mayor and/Regent. This mechanism is implemented gradually and transparently.